IMPLEMENTASI MODEL PROBLEM BASED LEARNING (PBL) PADA MATERI SUMBER ENERGI MELALUI EKSPERIMEN LAMPU DARI MINYAK DAN AIR DI SDN 188 BUNGA RAYA - Putri Handayani, Wulandari; Neni Hermita, Rifqa Gusmida Syahrun Barokah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effectiveness of implementing the Problem Based Learning (PBL) model through a lamp experiment using cooking oil and water in enhancing third-grade students’ understanding of energy sources. The research was conducted at SDN 188 Bunga Raya involving 25 students. A descriptive quantitative method was used, with data collected through observation, tests, and documentation. Students were divided into groups to carry out a simple experiment designed to connect science learning with meaningful real-life experiences. The results showed that 80% of groups achieved mastery based on group worksheets, and 88% of students scored above the Minimum Mastery Criteria in the individual evaluation. These findings indicate that the PBL approach combined with simple experiments is effective in improving students’ conceptual understanding of energy, creating meaningful, engaging, and contextually relevant learning experiences.